2016
DOI: 10.1016/j.annepidem.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative bias analysis in an asthma study of rescue-recovery workers and volunteers from the 9/11 World Trade Center attacks

Abstract: Purpose When learning bias analysis, epidemiologists are taught to quantitatively adjust for multiple biases by correcting study results in the reverse order of the error sequence. To understand the error sequence for a particular study, one must carefully examine the health study’s epidemiologic data-generating process. In this manuscript, we describe the unique data-generating process of a man-made disaster epidemiologic study. Methods We described the data-generating process and conducted a bias analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Techniques exist to adjust study results for biases in epidemiologic studies including bias analyses, 41,42 yet challenges with specifying the bias parameters remain. 43 Various data sources are needed to develop and understand overall AE profiles of consumer products. Inconsistent coding terminology to describe AEs across data sources precluded our ability to make direct analytical comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques exist to adjust study results for biases in epidemiologic studies including bias analyses, 41,42 yet challenges with specifying the bias parameters remain. 43 Various data sources are needed to develop and understand overall AE profiles of consumer products. Inconsistent coding terminology to describe AEs across data sources precluded our ability to make direct analytical comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The reported AE verbatims are then coded to MedDRA lower‐level terms and aligned to PTs that may be incorrect and result in further classification bias. Techniques exist to adjust study results for biases in epidemiologic studies including bias analyses, 41,42 yet challenges with specifying the bias parameters remain 43 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, quantitative bias analyses extend beyond the bounds of data accuracy: similar approaches can handle cases of selection bias and residual confounding (again, see Lash et al, 2009 , and Smith et al, 2021 ). Beyond the case study demonstrated in this article, we refer readers to these other examples of quantitative bias analysis applied to misclassified outcome data ( Bodnar et al, 2010 ; Burstyn et al, 2020 ; Goldstein et al, 2016 ; Goldstein et al, 2021 ; Jurek & Maldonado, 2016 ; Srugo et al, 2021 ; Wesselink et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disaster epidemiology is defined as the epidemiologic investigation of disaster forecasting and warning, emergency responses according to the different phases of disasters, and the short-and long-term adverse health effects of disasters on the population (7). Although disaster epidemiology is an evolving field, it still faces significant challenges (8).…”
Section: Introductionmentioning
confidence: 99%